Fossette_Whale_Environment_Data_2017 - Fossette, Sabrina; Abrahms, Briana; Hazen, Elliott L.; Bograd, Steven J.; Newton, Kelly M.; Calambokidis, John; Burrows, Julia A.; Goldbogen, Jeremy A.; Harvey, James T.; Marinovic, Baldo; Tershy, Bernie; Croll, Donald A. (Dryad Digital Repository, 2017)
Monthly values of environmental variables and whale densities used in the manuscript.